A techno-economic analysis of thermochemical conversion of solid wastes for biofuel production in Malaysia - Chin, Ching Cheon (2023)
Municipal solid waste (MSW) has long been used around the world for the production of biofuel and electricity. Malaysia, on the other hand, falls behind other countries in using MSW as a source of energy or biofuels, despite relying largely on landfills for MSW disposal. More efficient waste management is desperately needed in Malaysia because of worries about greenhouse gas emissions and scarce land. By applying waste-to-energy (WTE) techniques to MSW management, the study aims to assess the tecno-economic component of the energy, economic, and environmental (3E) impact of creating biofuels and renewable energy generation. The 3E assessment demonstrates that incineration is the superior choice considering both electricity and heat production. However, AD is more favourable when electricity production is the primary consideration. According to the findings, incineration (Scenario II) has the capacity to recover 1200 MWh per day, whereas AD (Scenario III) and gasification (Scenario IV) recover around 1050 MWh and 1000 MWh per day, respectively. The landfill gas recovery system (LFGRS) (Scenario I) technology produced the least quantity of recovered energy, approximately 275 MWh per day. Furthermore, the environmental analysis revealed that incineration has the potential to save approximately 1611 tCO2 per day, while anaerobic digestion and gasification have the potential to save approximately 1805 tCO2 per day and 1969 tCO2 per day, respectively, while LFGRS has the potential to save approximately 1729 tCO2 daily. The potential total costs related to each WTE technology were reviewed. The results of the total cost exhibited that AD had the lowest total cost of USD 93575 per day, while incineration and gasification had total cost of USD 147900 and USD 250400 per day respectively. The overall costs associated with each technology were also calculated. The study also revealed that the integrated WTE scenarios have demonstrated potential favourable results, where the combination of AD and incineration (Scenario V) provides potential energy output of 1110MWh per day of electricity, and 1105 MWh per day of heat generation, under a potential lower total cost per day of USD115,305, with a low carbon emission value of 1728 tCO2 per day.